Public Speaking as a Tool for Improving Students’ Speech Skills - Jamshidovna, Erkinova Sevinch; Aripova, M. (European Journal of Life Safety and Stability (2660-9630), 2023)
Public speaking included the presentation of one individual (speaker, rhetorician) before the crowd, with the speaker, relegated to a dynamic job, and the crowd - a detached one. At the current stage, the type of public discourse correspondence changes from talk to dialogic and is carried out in dynamic sorts and types of exchange - question, conversation, debate, interview, banter, and so on. Method for dialogization, including questions (explaining, logical, and so on) that permit you to lay out contact with the crowd, are intended to excite interest in discourse and keep up with the consideration of audience members. The improvement of explanatory abilities happens just on account of an effective public discourse, that is to say, the accomplishment of the objective. In such a manner, it’s a good idea to consider the construction of public discourse readiness, which incorporates three phases: pre-open (preliminary), open (essential), and post-open (logical). The motivation behind this study is to decide the circumstances for shaping and creating specialized college learners’ explanatory abilities throughout deciding the complex of expertly critical public talking abilities of learners of a specialized college.